Health literacy as mediator between perception of illness and self-medication behaviour among outpatients in the Kingdom of Saudi Arabia: implication to primary healthcare nursing - Eddieson Pasay-an; Reynita Saguban; Dolores Cabansag; Sameer Alkubati (BMC, 2024)
Abstract Introduction Perception of illness (PI) and self-medication (SM) have been thoroughly explored in the existing literature. However, there is a lack of understanding about the mediating effect of health literacy on PI and SM in a non-homogenous population like Saudi Arabia. As such, primary healthcare nurses who have constant interaction with the outpatients have difficulty addressing self-medication. This study aimed to investigate health literacy as mediator between PI and SM among outpatients in the Kingdom of Saudi Arabia (KSA). Methods This study employed a cross-sectional approach and was conducted at 10 major primary healthcare (PHC) clinics serving 30 million individuals in 13 different regions of KSA. The 424 outpatients who participated in this study were selected through convenience sampling. Data collection started in November 2022 and concluded in February 2023. Results The mean of the Brief Health Literacy Screening Tool, self-medication scale (SMS), and PI scores were 13.01 ± 3.32, 27.46 ± 7.01, and 45.56 ± 7.69, respectively. There was a significant relationship between the age and BRIEF scores (p = 0.039), and the level of education was significantly related to all variables, as were nationality and BRIEF scores (p = 0.001). Finally, occupation was significantly related to BRIEF and SMS scores (p = 0.001 and 0.003, respectively). Completing college and being non-Saudi had positively significant effects on health literacy (p < 0.01). The structural equation model (SEM) found no effect of PI on health literacy or SM behaviour (p = 0.263 and 0.84, respectively), but health literacy did have an effect on SM behaviour (p<0.001). Conclusion Health literacy is an important factor in self-medication behavior and that PI is not directly related to health literacy or self-medication behavior, but that health literacy does influence self-medication behavior. Therefore, primary healthcare givers should promote public health literacy alongside the control of other conditions as one of the most effective ways to decrease the prevalence of self-medication and the risks associated with it.